Effectiveness of Group Guidance Services Through Bibliotherapy Techniques in Increasing Students’ Tolerance - Putri, Junita Hanum Eka; Hasibuan, Ali Daud (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to determine the effectiveness of group counseling services using bibliotherapy techniques in improving student tolerance at State Junior High School 1 Natal. The background of this research is the low level of social tolerance among students, which is reflected through discriminatory behaviors such as teasing peers. The research was conducted from April to May 2025 using a pre-experimental approach and a one group pre-test–post-test design. The research population consists of all 90 seventh-grade students, with a sample of 10 students selected purposively. The data collection instrument is in the form of a tolerance scale, while the data analysis technique uses a paired sample t-test through SPSS version 25. The test results show a significance value (2-tailed) of 0.000 (p < 0.05), indicating a significant difference between the pre-test and post-test scores. Thus, it can be concluded that group guidance with bibliotherapy techniques is effective in increasing students’ tolerance. The implications of this research indicate that this service can be a strategic alternative in counseling interventions to shape students’ more tolerant character. The success of increasing tolerance is also noted.